2015
DOI: 10.1002/jmv.24188
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus mRNA testing for the detection of anal high‐grade squamous intraepithelial lesions in men who have sex with men infected with HIV

Abstract: Currently, screening for anal high-grade squamous intraepithelial lesions (anal HSIL) relies on anal cytology and high-resolution anoscopy. Since this approach has limited sensitivity and specificity for detecting anal HSIL, there is increasing interest in the role of biomarkers for predicting anal HSIL. The aim of this study is to evaluate the diagnostic accuracy of HPV E6/E7-mRNA expression for the detection of anal HSIL in MSM infected with HIV, in comparison to DNA-HR-HPV and anal cytology. This cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 22 publications
5
23
1
Order By: Relevance
“…Other studies have found that the sensitivity of E6/E7 mRNA for cervical HSIL was similar to HR-HPV DNA assays. 31, 32 It is not clear why the sensitivity of E6/E7 mRNA for anal HSIL appeared lower in our study. Our estimated sensitivity was similar when considering HSIL on histology alone, HSIL on cytology or HSIL on either test (data not shown).…”
Section: Discussioncontrasting
confidence: 68%
“…Other studies have found that the sensitivity of E6/E7 mRNA for cervical HSIL was similar to HR-HPV DNA assays. 31, 32 It is not clear why the sensitivity of E6/E7 mRNA for anal HSIL appeared lower in our study. Our estimated sensitivity was similar when considering HSIL on histology alone, HSIL on cytology or HSIL on either test (data not shown).…”
Section: Discussioncontrasting
confidence: 68%
“…Four studies evaluated the performance of E6/E7 mRNA for the detection of anal precancer and cancer, including a mix of HIV‐positive and HIV‐negative MSM (Supporting Table 1) . The pooled sensitivity and specificity of E6/E7 mRNA was 74.3% (95% CI, 68.3%‐79.6%) and 65.5% (95% CI, 58.5%‐71.9%), respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The observation that 12.6% of men with negative cytology at the baseline had a histological HSIL identified at that particular visit has been previously reported by our group . Others have reported false‐negative rates ranging from 11% to 81% . The high rate of histological HSILs in the anus with negative cytology may be related to the anatomical complexity of the anal canal, the size of the area sampled, and the blind sampling technique used in comparison with the sampling of the cervix under direct vision.…”
Section: Discussionmentioning
confidence: 66%
“…Several recent studies with a design similar to SPANC have reported performance characteristics of anal cytology, and these are presented in Table . None of these report changes in PPVs over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation